2009
DOI: 10.2196/jmir.1303
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on Internet Support Groups (ISGs) and Depression (2): What Is Known About Depression ISGs?

Abstract: Background Internet support groups (ISGs) are a popular means by which consumers with depression communicate online. A number of studies have evaluated the nature and impact of depression-specific ISGs. However, to date there have been no published systematic reviews of this evidence.Objective The aim was to systematically identify and summarize the available evidence concerning the scope and findings of studies of depression ISGs.Methods Three databases (PubMed, PsycINFO, Cochrane) were searched using over 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 28 publications
8
80
0
Order By: Relevance
“…Young people with developmental challenges may have few traditional care options and feel more comfortable anonymously or at a distance, to share experiences and try to learn new behaviors [43]. Comfortable with Internet-based chats and groups, they may even express ideas of self-harm, negative affective states, or pessimistic cognitions of other peers [44,45]. This is concerning, though, if these things are not shared with parents and/or professionals.…”
Section: Methodsmentioning
confidence: 99%
“…Young people with developmental challenges may have few traditional care options and feel more comfortable anonymously or at a distance, to share experiences and try to learn new behaviors [43]. Comfortable with Internet-based chats and groups, they may even express ideas of self-harm, negative affective states, or pessimistic cognitions of other peers [44,45]. This is concerning, though, if these things are not shared with parents and/or professionals.…”
Section: Methodsmentioning
confidence: 99%
“…The motivational framework comprises the elements of engagement and guidance by a professional social worker to enhance adherence (element 2) [21] and the opportunity to interact with peers to relate learned materials to participants' current concerns (element 3) [22][23]. With regard to element 2, a master's level social worker reviewed progress and conducted brief weekly MIs with participants via instant messaging (IM) chats to sustain adherence.…”
Section: Motivational Frameworkmentioning
confidence: 99%
“…Users of the internet for mental health problems are described as individuals with lower levels of social support (Ivanova, Lindner, & Dahlin, 2015), a median age of 40 years, more likely to be women and with high unemployment levels (Houston et al, 2002). However, a systematic review (Griffiths, Calear, Banfield, & Tam, 2009) found no definitive information on OF gender distribution, concluding that OF user ages commonly range between mid to late 20s and mid-40s. This lack of consensus highlights the need to identify the socio-economic demographics of forum users.…”
Section: Introductionmentioning
confidence: 99%